Asrama Indonesia Merdeka Sebagai Pembentuk Kader Muda Indonesia - Afifah Jasmine Krisdintami; Kurniawati Kurniawati; Umasih Umasih (Universitas Negeri Malang, 2022)
This study examines the role of a dormitory called Dormitory of Free Indonesia. This hostel was founded by a Japanese Navy officer, namely Rear Admiral Tadashi Maeda, in October 1944 with the aim of forming young Indonesian political cadres. The method used in this study is the historical method which includes five stages, namely the selection of topics with intellectual approaches, heuristics, verifications, interpretations, and historiography. Based on the results of the research, the Dormitory of Free Indonesia has played a role in forming young political cadres who will later take on roles after Indonesian independence through regeneration which is carried out in the dormitory. The regeneration activities at this dormitory include learning in classes for six months and martial arts taught directly by the Japanese army. Some of the students who graduated from Dormitory of Free Indonesia were Abdul Kadir Jusuf, Hasan Gayo, Sukarni, and Chaerul Saleh. There is controversy about the spread of communism in the dormitories, as historian Kahin points out. However, this news was later dismissed by national figures who taught at the Dormitory of Free Indonesia, including Admiral Maeda. Penelitian ini ini mengkaji peran dari sebuah asrama bernama Asrama Indonesia Merdeka. Asrama ini didirikan oleh seorang perwira Angkatan Laut Jepang, yaitu Laksamana Muda Tadashi Maeda, pada bulan Oktober 1944 dengan tujuan untuk membentuk kader-kader politik muda Indonesia. Metode yang digunakan dalam penelitian ini adalah metode historis yang mencakup lima tahapan, yaitu pemilihan topik dengan pendekatan intelektual, heuristik, verifikasi, interpretasi, dan historiografi. Berdasarkan hasil penelitian, Asrama Indonesia Merdeka berperan dalam membentuk kader-kader politik muda yang nantinya akan mengambil peranannya setelah kemerdekaan Indonesia melalui kaderisasi yang dilakukan di asrama. Aktivitas kaderisasi di asrama ini mencakup pembelajaran di kelas-kelas selama enam bulan dan seni bela diri yang diajarkan langsung oleh tentara Jepang. Beberapa murid-murid lulusan dari Asrama Indonesia Merdeka ialah Abdul Kadir Jusuf, Hasan Gayo, Sukarni, dan Chaerul Saleh. Terdapat kontroversi mengenai penyebaran paham komunis di dalam asrama, seperti yang dikemukakan oleh sejarawan Kahin. Namun, kabar ini kemudian ditepis oleh tokoh-tokoh nasional yang mengajar di Asrama Indonesia Merdeka, termasuk Laksamana Maeda.